El arte urbano: el hip hop y su impacto en la sociedad contemporánea - Piedra Ramírez, Ricardo Oswaldo (2015)
The main objective is to generate an artistic creation by the Street Art about Hip Hop culture, using contemporary art as a tool to carry out an interaction with the public. In our society the Hip Hop is still considered something no future and associated with gangs, vandalism and not as an urban tribe of many values. The problem lies in the lack of information and interpretation have about the same. Urban art is very broad, covering many street terms such as Street Art, Graffiti Art, Hip Hop and more. There are three different terms, when it comes to Hip Hop refers to a global culture, in which there are four: The Emceein, Breakin, Graffiti Art and Deejayin, while the word Hiphop refers to people who belong to the movement and to a lifestyle, and the word refers to hip hop Rap Product materialized. There are two different terms: Graffiti Art that is incorporated into the Hip Hop that has artistic fundamentals, however Graffiti element refers to a fact not associated with Hip Hop, lacks aesthetics and therefore anyone can do. The methodology used for experimental fields, the results are consistent, achieving desired fields by conceptual art and community raised from a psychological and historical view of society from the city. Free artistic event makes the viewer is the passer and street artist finds a way to expose, raise and attach the proposal in the right place. Delve from a personal aspect will come to find and discover new fields that make the work effective.